The city is made in the celebration: Peri-urban transformations in the patronal celebrations of Guadalajara - Samuel Hernández-Vázquez; Carlos Ríos-Llamas (Íconos)
Patronal celebrations are, par excellence, an artifact of memory. In the case of Tesistán, located along the rural-urban strip of Guadalajara, Mexico, three fundamental characteristics are noteworthy: First, the conservation of events have forged local identities; second, the fact that in celebration a juxtaposition is shown between rural and urban forms of life; third, the celebration expresses, above all, different modes of containment and resistance with regards to policies of urban expansion in the city of Guadalajara. The objective of this article is to analyze the mechanisms of collective memory, materialized in the patronal celebration dedicated to San Francisco de Asís, in relation with the tensions that the process of urbanization generates among those who inhabit Tesistán. Through ethnography, semi-structured interviews were conducted with actors and political figures of the locality who represent the organizing groups of the patronal festivities. As a main finding, it can be highlighted that, considering the celebration as an artifact of memory, one can better understand socio-territorial conflicts, the loss of community cohesion, the disassociation of the past, and the social dissolution caused by the transformation of the built space.